Driving performance of euthymic outpatients with bipolar disorder undergoing real‐world pharmacotherapy. Issue 5 (14th February 2022) - Yamaguchi, Akiko; Iwamoto, Kunihiro; Ando, Masahiko; Fujita, Kiyoshi; Yokoyama, Motonori; Akiyama, Tsuyoshi; Igarashi, Yoshio; Ozaki, Norio
Abstract : Objective: Medications for the treatment of bipolar disorder (BD) could affect patients' cognitive function. Patients with BD present with neurocognitive impairment even in a remission state. Little research is available on the daily functioning, especially driving performance, of stable outpatients with BD under pharmacological treatment. Methods: In total, 58 euthymic outpatients with BD undergoing real‐world pharmacotherapy and 80 sex‐ and age‐matched healthy controls (HCs) were enrolled. Three driving tasks using a driving simulator—road‐tracking, car‐following, and harsh‐braking—and three cognitive tasks—Continuous Performance Test, Wisconsin Card Sorting Test, and Trail‐Making Test—were evaluated. Symptom assessment scales—Young Mania Rating Scale, Structured Interview Guide for the Hamilton Depression Rating Scale, Beck Depression Inventory‐II, Social Adaptation Self‐evaluation Scale, and Stanford Sleepiness Scale—were also completed. Results: Car‐following and road‐tracking performance were significantly impaired in patients with BD compared with HCs after adjusting for demographic variables, but these performances generally overlapped. Broad neurocognitive functions were significantly lower in the patients with BD compared to HCs, but car‐following performance was significantly negatively correlated with sustained attention only. Although most patients received multiple medications rather than monotherapy, no relationship between prescriptions and driving performance was found. Conclusion: Euthymic patients with BD under steady‐state pharmacotherapy had impaired driving performance compared with HCs, but the overlapping distributions of driving performance suggested that driving performance is not always deteriorated in patients with BD. Therefore, attentional function may be a useful clinical feature for judging driving aptitude in patients with BD.